2007
DOI: 10.1159/000106981
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome as Function of Blood Pressure in Acute Ischemic Stroke and Effects of Thrombolysis

Abstract: Background: While baseline blood pressure (BP) is a known predictor of 90-day residual deficit after acute ischemic stroke, the effect of thrombolysis on this relationship has not been described. To study the interaction and to find intervals of prognostic significance, the functional forms of this predictive relationship should be found and compared for recombinant tissue plasminogen activator (rt-PA)- and placebo-treated patients of the first European Cooperative Acute Stroke Study. Methods: We studied the 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Rusanen et al ( 19 ) performed a retrospective analysis with 104 AIS patients with good collateral filling, finding that moderately elevated SBP was associated with good collateral circulation post IVT, however, inversely correlated with 3-month clinical outcome. Yong et al ( 20 ) found an S-shaped relationship between baseline BP with clinical outcome in AIS patients treated with IVT, based on the ECASS trial database. The above studies predated the effect of IVT on patients treated with MT.…”
Section: Discussionmentioning
confidence: 99%
“…Rusanen et al ( 19 ) performed a retrospective analysis with 104 AIS patients with good collateral filling, finding that moderately elevated SBP was associated with good collateral circulation post IVT, however, inversely correlated with 3-month clinical outcome. Yong et al ( 20 ) found an S-shaped relationship between baseline BP with clinical outcome in AIS patients treated with IVT, based on the ECASS trial database. The above studies predated the effect of IVT on patients treated with MT.…”
Section: Discussionmentioning
confidence: 99%
“…Higher initial values of SBP in patients with no history of hypertension were connected with increased risk of SICH secondary to thrombolysis [26]. Patients benefited from rt-PA in terms of no or negligible handicap after 90 days, without excess risk of death, with baseline SBP between 140 and 160 mm Hg or baseline DBP between 80 and 90 mm Hg [27]. In future studies the impact of blood We analysed only the period of early hospital treatment, but our results may be used in predicting longterm outcome and potential intensification of treatment in terms of secondary prevention, because, as shown by other authors, rapid neurological recovery is correlated with favourable outcomes assessed by 3-month mRS [10,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%